Behavioral and Evolutionary Perspectives on Visual Lateralization in Mating Birds: A Short Systematic Review - Soma, Masayo (Frontiers in Physiology, 2022)
The division of cognitive processing between the two hemispheres of the brain causes lateralized eye use in various behavioral contexts. Generally, visual lateralization is shared among vertebrates to a greater extent, with little interspecific variation. However, previous studies on the visual lateralization in mating birds have shown surprisingly huge heterogeneity. Therefore, this systematic review paper reviewed past research findings and systematically analyzed them using phylogenetic comparative methods. The review aimed to elucidate why some species used their left eye and others their right to fixate on individuals of the opposite sex, such as mating partners or prospective mates. It was found that passerine and non-passerine species showed opposite eye use for mating, which could have stemmed from the difference in altricial vs. precocial development. However, due to the limited availability of species data, it was impossible to determine whether the passerine group or altricial development was the primary factor. Additionally, unclear visual lateralization was found when studies looked at lek mating species and males who performed courtship. These findings are discussed from both evolutionary and behavioral perspectives. Possible directions for future research have been suggested.